Straff-välfärdsstaten och kontrollkultur i svensk kriminalpolitik - Tham, Henrik (Nordisk Tidsskrift for Kriminalvidenskab, 2019)
Swedish criminal policy has changed markedly in the years following World War II. This change shows clear parallels to the processes described in David Garland’s The Culture of Control. The current analysis, however, indicates that developments in Sweden differ in important ways from processes discussed by Garland. First, Garland’s hypotheses concerning factors that tend to increase crime and the fear of crime do not hold true for Sweden. Second, the notion that an increasingly punitive population has pressured its political representatives for more penal legislation and more prisons is not supported by the Swedish data. Third, the movement toward a harsher criminal policy may actually have resulted from dynamics within the welfare state itself. The punitive turn should therefore be understood as a political change from above rather than a cultural change from below.